Complex osteoclastogenic inductive effects of nicotine over hydroxyapatite. Issue 2 (5th June 2017) - Costa‐Rodrigues, Joao; Rocha, Isabel; Fernandes, Maria H.
Abstract : Cigarette smoke is associated to pathological weakening of bone tissue, being considered an important playmaker in conditions such as osteoporosis and periodontal bone loss. In addition, it is also associated with an increased risk of failure in bone regeneration strategies. The present work aimed to characterize the effects of nicotine on human osteoclastogenesis over a hydroxyapatite substrate. Osteoclast precursors were maintained in the absence or presence of the osteoclastogenesis enhancers M‐CSF and RANKL, and were further treated with nicotine levels representative of the concentrations observed in the plasma and saliva of smokers. It was observed that nicotine at low concentrations elicit an increase in osteoclast differentiation, but only in the presence of M‐CSF and RANKL it was also able to significantly increase the resorbing ability of osteoclasts. A slight downregulation of NFkB pathway and an increase in the production of TNF‐α and, particularly PGE2, were involved in the observed effects of nicotine. At high concentrations, nicotine revealed cytotoxic effects, causing a decrease in cell density. In conclusion, nicotine at levels found in the plasma of the smokers, has the ability to act directly on osteoclast precursors, inducing its osteoclastogenic differentiation. The stimulatory behavior appears to be dependent on the stage of osteoclastic differentiation of the precursor cells, which means, in the absence of M‐CSF and RANKL, it only favors the initial stages of osteoclast differentiation, while in the presence of the growth factors, a significant increase in their resorbing ability is also achieved. Abstract : The effects of nicotine on human osteoclastogenesis was evaluated, in the presence of hydroxyapatite. At low doses, nicotine displayed a pro‐osteoclastogenic behavior, while at high doses, it was lethal to the cells. The observed effects were accompanied by significant changes in important intracellular signaling pathways, as well as in the producation of TNF‐alpha and PGE2.